Professional Worldview as a Determinant of The Slavic Cultural Archetype and Its Transformation into Pedagogical Forms - Sizov, Vitalii; Slavska, Yanina; Alforov, Oleksandr (Journal of History Culture and Art Research, 2022)
In the article, the problems of educational methodology from the sociocultural perspective are considered. The main task of the study is to analyze the characteristic manifestations of the cultural archetype of Orthodox-Slavic society and their reflection in the sphere of practical pedagogy. The elements (features) of the cultural archetype that determine social behavior, including pedagogical practice, are generally highlighted in the research. The article covers some of the features of pedagogical theory and practice in comparison of «West-Orthodox East», and the authors attempt to relay socio-cultural models on the pedagogical model. The pattern of this retransmission is beyond doubt because the education system itself, firstly, naturally copies the social and cultural system in the present and secondly, tends to reproducing of existing socio-cultural relations in the future. The second thing is the most important one. There can be changes in society only if there are changes in education because education is one of the few social institutions that shape thinking in the long view. The analysis of the sources characterizing the cultural archetype of the Slavic-Orthodox society and its reflection in the system of pedagogical processes shows the direct and logical interdependence of the two phenomena. The cultural archetype of society in many ways passionately determines the pedagogical forms and the pedagogical process itself regardless of its organisational forms which are sometimes directly borrowed from a foreign cultural pedagogical system. This is where the problem of methodology in organizing pedagogical approaches to organizing the education and upbringing system is manifested. Hence, the theme of cultural relativism (poly-culturalism) is actualized which essentially defends the position of the uniqueness of the cultures of particular countries and at the same time does not reject the system of world progressive development.